The moment map and the group of volume-preserving diffeomorphisms: applications to differential geometry (2023)
In this work, we use this moment map to relate solutions to certain differential equations to (i) diffeomorphisms of compact Riemann surfaces, (ii) additional Kähler metrics on a given compact Kähler manifold, and (iii) symplectic forms on 4-manifolds.